Development of a Lumped Parameter Model of Human Whole Body Circulatory Loop - Xun Liu; Chenghuai Mo; Jiaxing Li; Hongyi Yu; Sheng Hu; da Zhu; Puming Zhang; Yonghua Li (IEEE Access)
The simulation of human cardiovascular dynamics is essential for understanding organ pathology and advancing cardiovascular assistive devices. However, a notable gap remains in defining comprehensive hemodynamic parameters for testing ventricular assist devices and studying prevalent cardiovascular diseases. This study introduces a lumped parameter model of the human circulatory system with two distinct loops. Utilizing this model, the hemodynamic characteristics of circulatory loops in healthy individuals, heart failure patients, and those experiencing cardiogenic shock are investigated, alongside transitions in circulatory states throughout the day. The model further simulates the pathological processes of two typical cardiovascular diseases: aortic valve stenosis and mitral valve regurgitation through parameter adjustments. Results demonstrate that the model effectively captures the essential parameters of both systemic and pulmonary circulation, providing insights into clinical pathophysiological phenomena through the generated curve variations. By fine-tuning the model to reflect various pathological conditions, precise simulations of prevalent cardiovascular diseases are achieved, deepening the understanding of their underlying mechanisms. Findings align closely with clinical data, highlighting the model’s potential as a valuable tool for device development and pathological research in the cardiovascular field.